ANCAMAN PERANG SIBER DI ERA DIGITAL DAN SOLUSI KEAMANAN NASIONAL INDONESIA - Salomon A.M. Babys (FISIP Universitas Bung Karno, 2021)
Abstract This article aims to explain the meaning, forms, and threats of cyberwar against the Indonesian nation and State as well as the solutions offered to be implemented by the Indonesian people in anticipating the possibility of cyberwar by other countries against the Indonesian nation. This study uses a descriptive analysis methodology by taking information from journal articles that discuss cyber warfare. Cyberwar can be said as war through the penetration of computer systems, networks, information, and communications of other countries with the aim of damaging or creating disturbances so that the country being fought can be controlled either directly or by direct action. Cyberwarfare is identical to hybrid warfare, namely war that is complex in nature, because it can start from cybercrime, but will continue to develop towards cyberwar. The various forms of cyber warfare include Hacking, Cyber sabotage/sabotage, espionage, Cyberattack, Garding, Spyware, Vandalism, and attacks on electricity networks or vital elements of a country. Indonesia has experienced crimes or cyber wars with other countries, and Indonesia has responded by taking several anticipatory efforts including encouraging cyber security cooperation, forming regional and international agreements or norms, and building institutions. non-military national cyber to anticipate it. All anticipatory efforts by the Indonesian state are basically very positive and ideal, but there are weaknesses in the development of cyber military strength, the development of the national satellite itself, and the formation of legislation that is still not perfect to minimize the realization of cyberwar.